Merdeka Belajar pada Perspektif Pendidikan Kelurga Di Era Pandemi COVID 19 - Fatmi Fatmi; Firman Firman; Rusdinal Rusdinal (CV. Syntax Corporation Indonesia, 2021)
The purpose of this research is to describe the freedom of learning in the era of pandemic covid 19 with a family perspective. This research is a research library research, which is basically qualitative research by Analyzing how to instill family education in the concept of freedom of learning during the pandemic covid 19 by means of distance learning (PJJ) which is currently an alternative in order to run the learning process and in meeting the demands of the curriculum in order to be achieved well. Based on the discussion, it can be concluded that: freedom of learning is an alternative learning approach that is currently rolling and becoming a national policy. Surely as a good citizen and have a filter power against the family, then go home to each family.